MODERN METHODOLOGIES IN ENGLISH LANGUAGE TEACHING - Jo'rayeva Sultonposhsho Akram qizi (Web of Journals Publishing, 2026)
The field of English language teaching has undergone significant transformations over the past decades, particularly with the recognition of the need to adapt methodologies to the ever-changing educational landscape. Traditional teacher-centered approaches have gradually given way to student-centered paradigms, reflecting a richer understanding of language acquisition as a complex, interactive process. Educators now embrace a vast array of techniques and strategies, aiming to develop not only the linguistic competence of learners but also their communicative and intercultural competencies. These developments are rooted in linguistic theory, cognitive science, and educational psychology, all converging to create a more holistic and effective framework for teaching English as a second or foreign language.
Keywords: Modern teaching methods, communicative approach, blended learning, task-based learning, technology integration, student-centered learning, differentiated instruction, formative assessment, interactive activities, language proficiency.